Criminal Offences against Public Health under the Criminal Code of the Republic of Slovenia - Jakulin, Vid (Medicine, Law & Society, 2020)
The author discusses criminal offences against public health under the Criminal Code of the Republic of Slovenia. In this Chapter of the Criminal Code, the object of protection under criminal law is human health, i.e. the health of both individuals and people in general as a common (general) value. Although criminal offences against public health are statistically insignificant in the author’s opinion, they are important for protecting human health as one of the most significant values protected by law. Given the rapid development of medicine, it may be expected that the need will arise in the future for some new incriminations. Modern law places an increasing importance on an injured person’s approval for interference with his or her body, which will lead to a different way of assessing the completeness of the essence of several criminal offences, referred to in this Chapter of the Criminal Code.